Literature Review; The Effect of Buerger Allen Exercise on Ankle Brachial Index (ABI) Values in Diabetes Mellitus Type 2 Patients; Literature Review - Basmallah, Carmitha Nareswari; Farida, Imroatul; Badriyah, Fatin Lailatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
Introduction: Patients with Diabetes Mellitus type 2 Â tend to have ABI values lower than the normal range due to lack of physical exercise and uncontrolled hyperglycemia. This needs to be prevented through joint movement exercises with the Buerger Allen exercise which can increase blood perfusion in the lower extremities so that there is an increase in the value of the ankle-brachial index (ABI). Objective: This study aims to determine the effect of Buerger Allen exercise on the value of the ankle-brachial index (ABI) in patients with Diabetes Mellitus type 2 based on a review of research journals. Methods: This study uses a literature review method. Search literature using 5 databases, namely Portal Garuda, Sinta, ProQuest, Scopus, and Google Scholar with keywords according to MeSH, namely